A psychosocial rehabilitation approach for a case of persistent urogenital sinus with ambiguous genitalia in a female adult - Chowdhary, Seema; Chowdhary, Arvind Kumar; Pandey, Sushma (Asian Journal of Medical Sciences, 2014)
Objective: Urogenital Sinus is a rare congenital deformity which overture to preclude of normal embryonic vaginal progression. We report a case of urogenital sinus with ambiguous genitalia in a female adult. Case Report: An unmarried young female aged 26 years presented to our hospital with amenorrhea of 6 months and history of urinary incontinence from childhood. The diagnostic features of this case include normal haemogram with mildly elevated blood urea and creatinine, normal 17 ketosteroids, serum testosterone and DHEA; bilateral moderate hydronephrosis with uterus of size 6.8 x 4.6 x 5.3 cm; urogenital sinus with partial separation of bladder and vagina-vaginal type; bilateral hydrouretronephrosis with mild renal cortical scarring and bicornuate unicollis uterus cervix opening into the urogenital sinus. She was diagnosed with persistent urogenital sinus (Vaginal type) without congenital adrenal hyperplasia, but with associated mullerian anomaly. Treatment option was a U-shaped vaginoplasty with an aim of widening vaginal introitus and advancement of hypospadiac external urethral meatus to prevent micturition into vagina. Conclusion: Though the possible treatment options were discussed, this case study emphasizes the need of psycho social rehabilitation for the proper treatment of ambiguous genitalia. DOI: http://dx.doi.org/10.3126/ajms.v6i4.10107 Asian Journal of Medical Sciences Vol.6(4) 2015 89-91